Designing a Production System for Woven ‘Stagen’ Products: a Community Service Practice in a Weaving Community - Kurniawan, V. Reza Bayu; Ma'arif, Syamsul; Irawan, Buntoro; Priyanto, Agung; Puspitasari, Fransiska Hernina; Bashir, Sibgha (Asian Journal of Community Services, 2024)
A robust production system needs to be implemented across all business scales, including small-scale enterprises managed by community groups. This forms the foundation for the development of more competitive businesses. As reported in this paper, a community service program was elaborated to design a production system for a stagen weaving business group located in Moyudan, Sleman, Indonesia. To implement this production system, there are five main stages: situational analysis, production system design, workshop, implementation, and monitoring and evaluation. A pilot project was tested on four weavers with distinct characteristics. The results indicate that each of the four weavers produced different stagen patterns with significant revenue gains for weaver 1 and weaver 2 amounting to more than IDR 500.000 (360.24 meters and 237.43 meters, respectively). This program successfully achieved specific targets in line with the scope.